2017
DOI: 10.4236/psych.2017.811114
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sexual Orientation on College Student Victimization: An Examination of Sexual Minority and Non-Sexual Minority Student Populations

Abstract: Our research examines the possible association of sexual orientation and self-reported sexual harassment, sexual assault, intimate partner psychological abuse, and intimate partner physical abuse of college students from a northeastern university in the United States. Understanding the prevalence of these behaviors within this age group is important, as developing appropriate college policy to reduce these actions at this time may be beneficial for future prevention. This study also allows for one of the few t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For example, Porter and Williams (2011) found that Deaf and Hard of Hearing students and sexual-minority students were more likely to experience physical and psychological abuse, and sexual minorities and racial minorities were more likely to experience sexual abuse in relationships than majority group members. In a study of college students, Beaulieu, Dunton, Williams, and Porter (2017) found that sexual-minority students were twice as likely to experience intimate partner physical abuse and 1.5 times more likely to experience psychological abuse from an intimate partner than students who did not identify as a sexual minority. This is consistent with other study findings that sexual-minority students are more likely to experience various forms of dating violence (Edwards et al, 2015).…”
Section: Intimate Partner Violence Among College Studentsmentioning
confidence: 99%
“…For example, Porter and Williams (2011) found that Deaf and Hard of Hearing students and sexual-minority students were more likely to experience physical and psychological abuse, and sexual minorities and racial minorities were more likely to experience sexual abuse in relationships than majority group members. In a study of college students, Beaulieu, Dunton, Williams, and Porter (2017) found that sexual-minority students were twice as likely to experience intimate partner physical abuse and 1.5 times more likely to experience psychological abuse from an intimate partner than students who did not identify as a sexual minority. This is consistent with other study findings that sexual-minority students are more likely to experience various forms of dating violence (Edwards et al, 2015).…”
Section: Intimate Partner Violence Among College Studentsmentioning
confidence: 99%
“…Correspondingly, it is plausible that heterosexual male victims may be least likely to report being raped, especially to the extent that they adhere to more traditional masculine gender role ideologies. However, both heterosexual men and woman are likelier to support traditional gender roles than their sexual minority counterparts (Kachel, Steffens, & Niedlich, 2016), which may also account for why the latter are more likely than the former to report various forms of sexual assault (Beaulieu, Dunton, McQuiller Williams, & Porter, 2017). Currently, there is very little research exploring whether stronger adherence to these belief systems influence disclosure rates or whether this may account for why being heterosexual and/or male associates with a decreased likelihood of reporting having been raped.…”
Section: The Current Studymentioning
confidence: 99%
“…LGBTQ+ college students also experience an elevated risk of sexual assault in relation to their heterosexual and cisgender peers (Cantor et al, 2017; Smith et al, 2016). Students who identify as sexual minority men are over nine times as likely to have experienced sexual assault as heterosexual male students, and students who identify as sexual minority women are over twice as likely as heterosexual female students to have been sexually assaulted in the past year (Beaulieu et al, 2017). Identifying as a gay man, bisexual, or questioning is associated with greater sexual assault victimization odds (Coulter et al, 2017; Johnson et al, 2016).…”
mentioning
confidence: 99%
“…Identifying as a gay man, bisexual, or questioning is associated with greater sexual assault victimization odds (Coulter et al, 2017; Johnson et al, 2016). Transgender college students also face higher rates of sexual assault victimization than cisgender students (Beaulieu et al, 2017; Cantor et al, 2017; Coulter et al, 2017; Johnson et al, 2016). Further, racial and ethnic identity is a risk factor for some groups of LGBTQ+ people of color, notably for men students of color (Beaulieu et al, 2017) and Black transgender students (Coulter et al, 2017).…”
mentioning
confidence: 99%